A Warming Inhale, Ecology and Capitalism in the Site of the Body - Gilson, Geoff (Auckland University of Technology, 2017)
Is my art anything? Is my politics nothing? This exegesis plays with ideas found in somatic research, literature on ecology and capitalism, activism and performance; it acknowledges theoretical research, bodywork and body rest, object-making, and participation, with the intention of avoiding the foregrounding of any of these over others. This egalitarian approach to art-making requires openness to the benefits of theoretical discourse and physical practice however that manifests, and to this end, content can be drawn from many sources. Within the context of late capitalism, ecological collapse and egoistic entitlement, I openly include methods of uncertainty and clutter in both body practice and mental/emotional processes that question my own hypocrisy within capitalism, and guilt as a participant in planetary demise. My research project uses a participatory performance model to attend to political issues through research on the intersection between the embodiment of personal trauma and planetary ecological trauma. I develop themes in my work through strands that cross activist, performative and participatory modalities, and bring these together in an ecologically-invested performance.
Keywords: Somatic; Ecology; Performance; Dance; Circus; Protest; Participation; Body